2000
DOI: 10.1046/j.1365-2958.2000.02109.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of two arginine residues in domain II, loop 2 of Cry1Ab and Cry1Ac Bacillus thuringiensisδ‐endotoxin in toxicity and binding to Manduca sexta and Lymantria dispar aminopeptidase N

Abstract: SummaryTwo arginine residues (368±369) of Cry1Ab and Cry1Ac were mutated to alanine, glutamic acid and lysine by site-directed mutagenesis. Insecticidal activities of the mutant toxins on Manduca sexta and Lymantria dispar larvae were examined. Cry1Ac mutant toxins (c)RR-AA and (c)RR-EE and Cry1Ab mutant toxins (b)RR-AA and (b)RR-EE showed great reductions in toxicity against both insects. In contrast, conservatively changed (c)RR-KK and (b)RR-KK mutants did not alter toxicity to either insect. Binding assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…1) The dissociation constants obtained during the course of this study are the maiden observations for a heterologously expressed and purified aminopeptidase receptor from any insect against Cry1Ac. Earlier studies have reported overall binding affinities using the surface plasmon resonance protocol against insect aminopeptidases purified from brush border membrane vesicles of the midgut (28 -30 (31,32). The off rates for dissociation calculated in this study for HaAPN1 with Cry1Ac works out to 2.08 ϫ 10 Ϫ6 s Ϫ1 , which is the lowest recorded for any APN/Cry protein interaction.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…1) The dissociation constants obtained during the course of this study are the maiden observations for a heterologously expressed and purified aminopeptidase receptor from any insect against Cry1Ac. Earlier studies have reported overall binding affinities using the surface plasmon resonance protocol against insect aminopeptidases purified from brush border membrane vesicles of the midgut (28 -30 (31,32). The off rates for dissociation calculated in this study for HaAPN1 with Cry1Ac works out to 2.08 ϫ 10 Ϫ6 s Ϫ1 , which is the lowest recorded for any APN/Cry protein interaction.…”
Section: Discussionmentioning
confidence: 71%
“…Also, the preliminary data of catalytic and Cry1Ac-interfering domain mapping suggests that the two domains do not overlap and may reside at different positions on the APN polypeptide. The lower values of dissociation obtained might be due to the fact that the APN employed in this study has been heterologously expressed and purified, whereas earlier studies relied on APN purified from brush border membrane vesicles of the host insect midgut (32).…”
Section: Discussionmentioning
confidence: 93%
“…Also, we analyzed the binding of Cry1Ab mutants located in regions of domain II and domain III previously characterized as APN-binding epitopes (27,28). Our data suggest that both APN and ALP are functional receptor molecules that bind the oligomeric structure of Cry1Ab toxin with high affinity, facilitating membrane insertion and pore formation, and we also found that ALP may a have a predominant and more important role in Cry1Ab toxicity at earlier stages of larval development.…”
mentioning
confidence: 58%
“…Cry1Ab-binding Regions Involved in APN and ALP Interaction-Domain II loop 2 and 3 mutants were previously shown to be affected in APN binding (27,37,38). Also, a scFv antibody that bound the domain III ␤16-␤22 region competed the binding of Cry1Ab to APN (10).…”
Section: Analysis Of Binding Of Cry1abmentioning
confidence: 99%
“…In another study, additional Cry1Ac derivatives with mutations at loop 2, loop 3, and loop ␣8 were tested for their abilities to bind to purified L. dispar APN, and each showed decreased binding to only one of the two proposed APN binding sites (82). A subsequent study showed that loop ␣8 mutants also decreased binding to purified M. sexta APN (103).…”
Section: Other Receptorsmentioning
confidence: 99%